Anthropocene monument as an ecotourism destination in the Special Region of Yogyakarta, Indonesia - Ajie Wicaksono; John JOI Ihalauw; Damiasih Damiasih (Journal of Enterprise and Development (JED), 2023)
Purpose — This study aims to analyze the procurement and processing of plastic waste from the Piyungan Integrated Waste Disposal Site (TPST) for the construction of Monument of Anthropocene (MoA) as a means of promoting ecotourism, while also examining the obstacles encountered during the monument-building process.Method — This research utilizes qualitative descriptive methods, which involve describing a phenomenon occurring within the community. The study was conducted at the Anthropocene Monument, employing data collection techniques such as observation, documentation, and interviews, with an interview conducted with the curator of the Anthropocene monument. The acquired data is analyzed using the Miles and Huberman analysis, encompassing data reduction, data presentation, and drawing conclusions.Result — The building process of MoA involves the use of bricks made from plastic waste. In addition to its function as a building, MoA serves as a multifaceted hub that fosters learning, exploration, information sharing, knowledge exchange, and collaborative efforts in production and work. MoA represents a form of ecotourism that showcases a strong sense of responsibility towards the environment and local culture by transforming plastic waste into valuable resources, both as raw materials in the form of bricks and as works of art. As an ecotourism site, MoA also offers three programs, namely art, culture, and circular economy.Contribution — This research makes a valuable contribution to the existing literature on ecotourism as an innovative approach to plastic waste management in less explored tourist areas in Indonesia. Moreover, the study specifically introduces MoA as a new and unique tourist destination.